Concurrent validity of countermovement and squat jump height assessed with a contact mat and force platform in professional soccer players - Ruf, Ludwig; Altmann, Stefan; Müller, Katharina; Rehborn, Anja; Schindler, Fabian; Woll, Alexander; Härtel, Sascha (Frontiers in Sports and Active Living, 2024)
Purpose The aim of this study was to assess the concurrent validity of a contact mat against force plates to measure jump height in countermovement jump (CMJ) and squat jump (SJ) in professional soccer players. Methods 23 male professional soccer players performed the CMJ and SJ, which were concurrently recorded using a portable contact mat (SmartJump) and a portable dual force plate system (ForceDecks). Equivalence testing between both systems (contact mat vs. force plate) and the two methods (impulse-momentum vs. flight-time and flight-time vs. flight-time) was performed compared to equivalence bounds of ±1.1 cm for the CMJ and ±1.6 cm for the SJ. Additionally, 95% Limits of Agreement (LoA) and intraclass correlation coefficients (ICC) were computed. Results Mean differences for the impulse-momentum vs. flight-time comparison for CMJ [3.2 cm, 95% CI (2.3–4.1)] and SJ [2.7 cm, (1.8–3.6)] were non-equivalent between both systems. LoA were larger than the equivalence bunds for CMJ and SJ, while ICCs were good [CMJ, 0.89, (0.76–0.95)] and excellent [SJ, 0.91, (0.79–0.96)]. As for the flight-time vs. flight-time comparison, mean differences were non-equivalent for the CMJ [1.0 cm (0.8 to 1.2 cm)] and equivalent for the SJ [0.9 cm (0.7–1.1 cm)]. LoA were narrower than the equivalence bounds for CMJ and SJ, while ICCs were excellent [CMJ, 0.995, 95% CI (0.989–0.998); SJ, 0.997, 95% CI (0.993–0.997)]. Conclusion Our findings indicate that the SmartJump contact mat cannot be used interchangeably with the ForceDecks force platform to measure jump height for the CMJ and SJ.